2003
DOI: 10.1128/iai.71.4.2292-2295.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Fibronectin-Binding Proteins of Staphylococcus aureus May Promote Mammary Gland Colonization in a Lactating Mouse Model of Mastitis

Abstract: The fibronectin-binding proteins (FnBPs) of Staphylococcus aureus are believed to be implicated in the pathogen's adherence to and colonization of bovine mammary glands, thus leading to infectious mastitis. In vitro studies have shown that FnBPs help the adhesion of the pathogen to bovine mammary epithelial cells. However, the importance of FnBPs for the infection of mammary glands has never been directly established in vivo. In this study with a mouse model of mastitis, the presence of FnBPs on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 29 publications
1
34
0
2
Order By: Relevance
“…S. aureus expresses a series of adhesins which can facilitate the organism's adherence to and/or invasion of nonphagocytic cells by interacting with extracellular matrix components of the host, such as collagen, fibrinogen, and fibronectin (17). Although there are some contradictory results from different models of infection (7,8,16,35,40,44,48), fibronectin-binding proteins are the main surface-associated proteins that function as adhesins and invasins by assembling the extracellular matrix protein Fn, which bridges to host cell receptors, such as ␣ 5 ␤ 1 -integrin (13,19,54). It has been demonstrated that fibronectinbinding proteins play a critical role in S. aureus infective endocarditis (35,50,60) and osteomyelitis (32,42).…”
Section: Discussionmentioning
confidence: 99%
“…S. aureus expresses a series of adhesins which can facilitate the organism's adherence to and/or invasion of nonphagocytic cells by interacting with extracellular matrix components of the host, such as collagen, fibrinogen, and fibronectin (17). Although there are some contradictory results from different models of infection (7,8,16,35,40,44,48), fibronectin-binding proteins are the main surface-associated proteins that function as adhesins and invasins by assembling the extracellular matrix protein Fn, which bridges to host cell receptors, such as ␣ 5 ␤ 1 -integrin (13,19,54). It has been demonstrated that fibronectinbinding proteins play a critical role in S. aureus infective endocarditis (35,50,60) and osteomyelitis (32,42).…”
Section: Discussionmentioning
confidence: 99%
“…In the work of Salasia et al (36), fnbA was more common than fnbB in S. aureus isolates originating from cows with bovine mastitis in Indonesian and German dairy herds. The proteins FnBPA and FnBPB enable the attachment of S. aureus to host tissues, facilitate the invasion of the organism into epithelial cells (4,48), and are involved in the colonization of other surfaces like medical devices (11). Strains not expressing FnBPA and FnBPB were demonstrated previously to have highly reduced abilities to invade bovine mammary epithelial cells in vitro (5).…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, often conflicting results have been reported that argue for (3,22,29,38,49) or against (2,5,10,33,41) their role as virulence factors in a given model in vivo. In most situations, the adhesive and invasive functions of FnBPs are the likely functional link in pathogenicity.…”
mentioning
confidence: 99%